PENGEMBANGAN SISTEM INFORMASI PENDATAAN BEDAH RUMAH BERBASIS WEB PADA DINAS PERUMAHAN RAKYAT DAN KAWASAN PEMUKIMAN DI KABUPATEN SUMBAWA - Dendi Saputro; I Made Widiarta; M. Julkarnain (Jurnal Informatika Teknologi dan Sains, 2020)
Housing and Settlement Area Office of Sumbawa Regency has a role in the architecture of urban layout and provide community service in government programs, including unlivable house renovation. The data recording is done manual basis, it generates difficulties to custodian when recording data for different location. Development of information system for unlivable housing assistance distribution e.g. unlivable house renovation on web basis in The Agency of Citizens Residential and Settlement Areas (PRKP) in Sumbawa Regency is designed to facilitate and integrated citizen recording system and to review the citizen that will receive the assistance from unlivable house renovation. This application is developed using Hypertext Preprocessor language program (PHP), MySQL database and the system development uses Waterfall method. The result of research is the citizens recording data who will receive an assistance from unlivable house renovation program, all citizens data and report of citizens that receive the assistance.